Clonagem e expressão do gene que codifica o inibidor de quimotripsina de Erythrina velutina WILLD. - caracterização e avaliação de seu potencial farmacológico - Amorim, Ticiana Maria Lúcio de (2014)
Proteinases are enzymes distributed widely founded in several organisms and perform many different functions, from maintaining homeostasis to the worsening of some diseases such as cancer, autoimmune diseases and infections. The proteins responsible of controlling the action of these enzymes are the inhibitors, that are classified based on their target proteases and are founded since simple organisms, such as bacteria, to higher organisms, such as larger plants and mammals. Plant proteinase inhibitors act by reducing or inactivating the activity of target proteases, thus, these proteins have been studied as potential tools in the treatment of diseases related to protease activities. In this context, an inhibitor of chymotrypsin from Erythrina velutina, called EvCI was previously purified and it was observed that this protein plays in vitro anticoagulant activity and anti-inflammatory activity in in vivo model. Aiming to reduce the environmental impact caused by the purification EvCI in high amounts and to facilitate the process of obtaining this protein, the recombinant chymotrypsin inhibitor from Eryhrina velutina was produced after cloning and expression in Escherichia coli. The bacteria were grown in LB medium and after induction of the expression this material was subjected to procedures for cell lysis and the product was applied on Nickel-affinity column. The proteins adsorbed were digested by thrombin and applied on Chymotrypsin-Sepharose affinity column, obtaining the purified inhibitor, named recEvCI. After electrophoresis, the recombinant inhibitor showed an approximately molecular mass of 17 kDa, and reduced the chymotrypsin and elastase activities in vitro. The recombinant inhibitor was sequenced and was found similar amino acids residues when compared to other inhibitors deposited in the database, with some modifications. recEvCI showed high stability under pH variations and reducing conditions, maintaining its activity around 80%. This protein increased the blood coagulation time in vitro by acting on the intrinsic pathway and did not show cytotoxicity against strains of mouse 3T3 fibroblasts and RAW 264.7 macrophages. recEvCI showed microbicide activity related to release of nitric oxide and consequently the activation of macrophages, futhermore having proinflammatory effects assessed by increased release of TNF-α. These results indicate that recEvCI can be biotechnologically used as a new tool in the control of coagulation-related diseases as well as can be an activating agent of the immune system in immunosuppressed individuals